2013
DOI: 10.1002/pssa.201329363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic 1D nanoparticles on electrooptic properties of 5CB liquid crystal

Abstract: Electrooptic properties of mixtures of 4-cyano-40 -pentylbiphenyl (5CB) thermotropic liquid crystal with four different inorganic dopants: (i) MoSI nanowires, (ii) MnO 2 nanorods, (iii) Ag nanowires, and (iv) WS 2 nanotubes were investigated by a conventional optical measurement technique. The dopant concentrations were in the range from 0.1 to 0.5 wt%. In all mixtures aggregation of the 1D nanoparticle (1D-NP) material was observed, therefore electrooptic response was probed in the regions in-between the aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…[ 11 ] Rajh et al compared the effects of nanowires, nanorods, and nanotubes; they concluded that, due to the small aspect ratio, the nanorods showed more compatibility than the other nanomaterials. [ 12 ] In addition, 2D graphene fl akes doped in NLCs have improved electrooptic switching and dielectric anisotropy. [ 13,14 ] An investigation, like the one presented in this paper, combining two modern functional materials, liquid crystals and graphene oxide (GO), is not only of fundamental interest but also of applicational relevance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] Rajh et al compared the effects of nanowires, nanorods, and nanotubes; they concluded that, due to the small aspect ratio, the nanorods showed more compatibility than the other nanomaterials. [ 12 ] In addition, 2D graphene fl akes doped in NLCs have improved electrooptic switching and dielectric anisotropy. [ 13,14 ] An investigation, like the one presented in this paper, combining two modern functional materials, liquid crystals and graphene oxide (GO), is not only of fundamental interest but also of applicational relevance.…”
mentioning
confidence: 99%
“…[ 1,2 ] The incorporation of various nanomaterials into liquid crystals (LCs), and the complexity of their interaction, have recently attracted much interest. [3][4][5][6][7][8][9][10][11][12] The addition of nanoparticles (NPs) to liquid crystals produces composite materials with additional functionality, and tunable optic, electric, magnetic, or electrooptic properties. Both molecular and macroscopic bulk properties are modifi ed.…”
mentioning
confidence: 99%
“…Rajh and co-workers report electro-optic properties of mixtures of 4-cyano-4'-pentylbiphenyl (5CB) thermotropic liquid crystal with four different 1D inorganic nanoparticles [11]. The most profound effect was obtained for MnO 2 /5CB: a reduction of the threshold voltage by a factor of 1.7 and of the total switching time by a factor of 1.5.…”
Section: Dear Readersmentioning
confidence: 99%
“…Solubility of the nanoparticles in liquid crystal matrix is limited [4][5][6]. Authors of article [4] dissolved 0.3% of ferroelectric Sn 2 P 2 S 6 nanoparticles capped with oleic acid in liquid crystal and claimed no aggregation effect, however no photos of the mixtures were provided.…”
Section: Introductionmentioning
confidence: 98%
“…Authors of article [4] dissolved 0.3% of ferroelectric Sn 2 P 2 S 6 nanoparticles capped with oleic acid in liquid crystal and claimed no aggregation effect, however no photos of the mixtures were provided. Elongated particles of diameter from tens to hundreds of nanometers: MoSI and Ag nanowires, MnO 2 nanorods, WS 2 nanotubes, synthesized and used without surrounding ligands, added to liquid crystal at weight fraction in range 0.1-0.5%, caused aggregation effect and formation of two phase composition [5]. Usage of ligands with enhanced compatibility with liquid crystal molecules for gold nanoparticles made possible to dissolve maximum 0.2% of the nanoparticles in liquid crystal matrix [6].…”
Section: Introductionmentioning
confidence: 99%